-2 (x-1)-(x+1)=5
3x-1/4=x+2/3
-6x-1=x+2
Jak coś te 3x-1/4 to cały ułamek jak i tez z tym x+2/3 liczniki to 3x-1 a mianownik 4, x+2 liczniki a 3 to mianownik
jak coś temat równania.


Odpowiedź :

Odpowiedź:

[tex]-2(x-1)-(x+1)=5\\\\-2x+2-x-1=5\\\\-3x+1=5\\\\-3x=5-1\\\\-3x=4\ \ /:(-3)\\\\x=-\frac{4}{3}\\\\x=-1\frac{1}{3}\\\\\\\frac{3x-1}{4}=\frac{x+2}{3}\\\\3(3x-1)=4(x+2)\\\\9x-3=4x+8\\\\9x-4x=8+3\\\\5x=11\ \ /:5\\\\x=\frac{11}{5}\\\\x=2\frac{1}{5}\\\\\\-6x-1=x+2\\\\-6x-x=2+1\\\\-7x=3\ \ /:(-7)\\\\x=-\frac{3}{7}[/tex]